2012
DOI: 10.3892/mmr.2012.900
|View full text |Cite
|
Sign up to set email alerts
|

SLCO1B1 *15 haplotype is associated with rifampin-induced liver injury

Abstract: Abstract. The organic anion transporting polypeptide 1B1 (OATP1B1, encoded by SLCO1B1) plays an important role in the transport of endogenous and xenobiotic compounds, such as bile acids and rifampin. In this study, the association between OATP1B1 polymorphisms and rifampin hepatotoxicity was investigated using integrated population genetic analysis and functional studies. A total of 273 unrelated patients treated with rifampin were recruited. The allele frequencies were examined in patients with drug (rifampi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…While oral exposure has a higher acceptable margin of safety, the fact that exposure to concentrations of microcystin less than one order of magnitude higher than the current minimum standard of MC-LR can induce LDH release in hepatocytes indicates that current margins of safety should be re-evaluated. Recreational activity and incidental consumption of water with even only moderately elevated MC-LR could potentially lead to toxicity in vulnerable populations, including children, genetically predisposed populations with enhanced OATP1B1 activity (Li et al, 2012), and patients with ongoing liver disease. Given that patients rapidly proceed to ALF after acute MC-LR intoxication, exposure to even low levels could result in unacceptably high morbidity and mortality rates in the event of civilian exposure to a contaminated water source, especially given the likelihood that multiple microcystin species are commonly present in water simultaneously.…”
Section: 1 Discussionmentioning
confidence: 99%
“…While oral exposure has a higher acceptable margin of safety, the fact that exposure to concentrations of microcystin less than one order of magnitude higher than the current minimum standard of MC-LR can induce LDH release in hepatocytes indicates that current margins of safety should be re-evaluated. Recreational activity and incidental consumption of water with even only moderately elevated MC-LR could potentially lead to toxicity in vulnerable populations, including children, genetically predisposed populations with enhanced OATP1B1 activity (Li et al, 2012), and patients with ongoing liver disease. Given that patients rapidly proceed to ALF after acute MC-LR intoxication, exposure to even low levels could result in unacceptably high morbidity and mortality rates in the event of civilian exposure to a contaminated water source, especially given the likelihood that multiple microcystin species are commonly present in water simultaneously.…”
Section: 1 Discussionmentioning
confidence: 99%
“…In general, the development of DILI is associated with several important risk factors, such as advanced age, gender, malnutrition, complications of disease, alcohol intake, and genetic factors (11). In addition, many candidate gene studies reported associations between ATDILI and N-acetyltransferase 2 (NAT2) (11)(12)(13), cytochrome P450 2E1 (CYP2E1) (14), glutathione S-transferase M1 (GSTM1) (15), glutathione S-transferase T1 (GSTT1) (16), superoxide dismutase 1 (SOD1) (17), HLA-DQA1/DQB1 (18), and the solute carrier organic anion transporter family member 1B1 (SLCO1B1) (19).…”
mentioning
confidence: 99%
“…Rifampicin and pyrazinamide have also been reported to be hepatotoxic [29, 30]; however, the mechanisms for rifampicin-induced hepatotoxicity and pyrazinamide-induced hepatotoxicity are unknown and unpredictable [4]. Some speculated genetic variants, such as SLCO1B1 , have been linked to toxicity with rifampicin, although limited data are available to support this claim [29].…”
Section: Introductionmentioning
confidence: 99%
“…Some speculated genetic variants, such as SLCO1B1 , have been linked to toxicity with rifampicin, although limited data are available to support this claim [29]. No hepatotoxicity has been described for ethambutol.…”
Section: Introductionmentioning
confidence: 99%